A structural chemogenomics analysis of aminergic GPCRs: lessons for histamine receptor ligand design. (15th August 2013) - Kooistra, A J; Kuhne, S; de, I J P; Leurs, R; de, C
<x xml:space="preserve">Abstract</x> Background and Purpose Chemogenomics focuses on the discovery of new connections between chemical and biological space leading to the discovery of new protein targets and biologically active molecules. G‐protein coupled receptors (GPCRs) are a particularly interesting protein family for chemogenomics studies because there is an overwhelming amount of ligand binding affinity data available. The increasing number of aminergic GPCR crystal structures now for the first time allows the integration of chemogenomics studies with high‐resolution structural analyses of GPCR‐ligand complexes. Experimental Approach In this study, we have combined ligand affinity data, receptor mutagenesis studies, and amino acid sequence analyses to high‐resolution structural analyses of (hist)aminergic GPCR‐ligand interactions. This integrated structural chemogenomics analysis is used to more accurately describe the molecular and structural determinants of ligand affinity and selectivity in different key binding regions of the crystallized aminergic GPCRs, and histamine receptors in particular. Key Results Our investigations highlight interesting correlations and differences between ligand similarity and ligand binding site similarity of different aminergic receptors. Apparent discrepancies can be explained by combining detailed analysis of crystallized or predicted protein‐ligand binding modes, receptor mutation studies, and ligand structure‐selectivity relationships that identify local differences in essential pharmacophore features in the ligand binding sites of different receptors. Conclusions and Implications We have performed structural chemogenomics studies that identify links between (hist)aminergic receptor ligands and their binding sites and binding modes. This knowledge can be used to identify structure‐selectivity relationships that increase our understanding of ligand binding to (hist)aminergic receptors and hence can be used in future GPCR ligand discovery and design. Linked Articles This article is part of a themed issue on Histamine Pharmacology Update. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2013.170.issue‐1